Wind-induced collapse analysis of long-span transmission tower–line system considering the member buckling effect. Issue 1 (January 2019) - Tian, Li; Pan, Haiyang; Qiu, Canxing; Ma, Ruisheng; Yu, Qiqi
The collapse problem of transmission tower upon strong winds was well noted in past few years. This article analyses the wind-induced collapse problem of a long-span transmission tower–line system. The member buckling effect was particularly considered. In doing so, a three-dimensional finite element model of the long-span transmission tower–line system was established in ABAQUS based on a practical project. The transmission tower and line were simulated by the frame and truss elements, respectively. The nonlinear behavior of a compressive member was simulated using the Marshall model, and the nonconvergence of numerical calculation was set to be the collapse criterion. The critical wind speed, damage position, and collapse probability were obtained from a collapse analysis of the long-span transmission tower–line system under different wind attack angles. The collapse mechanism of the long-span transmission tower–line system under a wind attack angle of 45° was investigated, and an incremental dynamic analysis was performed to evaluate the collapse-resistant capacity of the transmission tower. The study reveals that the interaction between bending moment and shear deformation is critical to the collapse of transmission tower.